AQbD-guided stability indicating HPLC method for azelnidipine and chlorthalidone fixed-dose combination tablet: a green approach - Rajvi Agrawal; Rajendra Kotadiya (Journal of Taibah University for Science)
This study developed a stability-indicating RP-HPLC method for quantifying azelnidipine and chlorthalidone in fixed-dose formulations using Analytical Quality by Design (AQbD) principles. A Plackett-Burman design was used for factor screening, followed by risk assessment and optimization using a central composite design to evaluate the effects of the organic phase percentage, flow rate, and modifier concentration. Acetonitrile percentage was identified as the most critical factor. The optimized method employed a Reliant™ C18 Waters column with a mobile phase of 0.1% formic acid and acetonitrile (62:38% v/v), with chlorthalidone and azelnidipine eluting at 4.1 and 13.7 minutes, respectively. Validation showed the method's robustness, accuracy, and precision. Forced degradation studies confirmed its reliability for tablet formulation analysis, and an Analytical Greenness score of 0.55 highlighted its environmental sustainability. This method is efficient, simple, and well-suited for routine quality control in the pharmaceutical industry.